A model of impeller whirl for baffled mixing vessels. (April 2015) - Cudmore, G.C.; Holloway, A.G.L.; Gerber, A.G.
Abstract: A model of impeller whirl that provides stability limits and mean square radial deflections for industrial mixing vessels is introduced. The model has a linear form and includes contributions to the mass, damping, and stiffness that arise from fluid forces acting on the impeller. The fluid forces were derived from Large Eddy Simulation (LES) of a mixer with a pitched blade impeller rotating at speed N, and undergoing prescribed circular orbits of frequency Ω . Simulations were performed for Reynolds numbers, 10 ≤ Re ≤ 10 000, and subsynchronous whirl frequency ratios, − 1 ≤ Ω / 2 π N ≤ 1 . Model predictions of impeller whirl instability and mean square vibration amplitude were compared to experimental data from a laboratory scale mixer. The simplicity and economy of the new model allows its use in on-line diagnostics and operational planning.